206 An immune-competent tumor organoid platform to test novel immune checkpoint combinations targeting the receptor CD47 in triple negative breast cancer. (10th December 2020) - Stirling, Elizabeth; Willey-Shelkey, Ethan; Wilson, Adam; Skardal, Aleksander; Triozzi, Pierre; Terabe, Masaki; Miller, Lance; Soker, Shay; Soto-Pantoja, David
Abstract : Background: Immune checkpoint blockade therapy targeting PD-L1 has recently been approved for metastatic triple negative breast cancer (TNBC) patients. However, a 7% response rate calls for better models and strategies to stimulate TN-tumor immunogenicity to increase patient response. Overexpression of the receptor CD47 impairs innate and adaptive tumor immunosurveillance when engaged to its counter receptor SIRPα or ligand thrombospondin-1. Co-expression of CD47 and PD-L1 is implicated with disease progression in TNBC patients. We examined through murine models and tumor organoid platforms whether targeting CD47 sensitizes TNBC tumors to PD-L1 therapy, focusing on the modulation of cellular bioenergetics as a potential mechanism and potentially predict response. Methods: The effects of targeting CD47 and PD-L1 were examined through orthotopic syngenic 4T1 and EMT-6 TNBC murine models. Due to predicting patient therapeutic response challenges, tumor organoid platforms investigated mechanisms of tumor sensitization to anti-PD-L1 by targeting CD47. Organoids were constructed by embedding murine TNBC tumor tissue and AH1 CD8+ T cells in a specialized ECM mimicking hydrogel. Immunohistochemistry was performed on organoid, human and murine TNBC tumor tissue. Cellular bioenergetics was analyzed through Seahorse® bioanalyzer. Results: Staining of human TNBC biopsies found elevated CD47 expression, signifying a potential therapeutic target. Targeting CD47 or in combination with anti-PD-L1 resulted in decreased tumor volume and weight in a TNBC murine model. The decrease in tumor burden was correlated with increased intratumoral granzyme B secreting CD8+ T cells. Additionally, targeting CD47 within organoids increased IFNγ and granzyme B released, indicating enhanced CD8+ T cell cytolytic capacity. Differential cellular bioenergetics was observed between cancer and T cells suggesting a shift in metabolism in the tumor microenvironment. CD47 targeted T cells had an increased glycolytic rate compared to WT T cells. Conversely CD47 targeted TNBC cells had a decreased glycolytic rate, which may be correlated with decreased PD-L1 expression. Conclusions: Targeting CD47 enhanced granzyme B and IFNγ expression suggesting potential mechanisms to increase tumor immunogenicity. CD47 targeted monotherapy or combination with anti-PD-L1 preserves T cell bioenergetics and antitumor function, resulting in decreased TNBC tumor burden. Alternatively, CD47 targeted TNBC had a decreased glycolytic rate and decreased PD-L1 expression, which is reported to regulate glycolysis through Akt/mTOR signaling. Targeting CD47 on T cells enhances their bioenergetics and antitumor function while decreasing TNBC cell bioenergetics, making them more susceptible to immune cell killing. Our data indicates that CD47 targeted monotherapy or combination with anti-PD-L1 may enhance TNBC patient response and improve overall survival. Acknowledgements: DSP and SS are supported by the Wake Forest Comprehensive Cancer Center Breast Cancer Center of Excellence Pilot Award. DSP is also supported by the ASTRO-BCRF Career Development Award (637969) while ERS is supported by NIGMS T32 (GM127261). Ethics Approval: Animal studies were approved by the Institutional Care and Use Committee, Wake Forest Health Sciences.